2011
DOI: 10.1103/physrevx.1.021016
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Gigahertz and Terahertz Surface Electromagnetic Waves with Metamaterial Resonators

Abstract: We computationally and experimentally investigate the use of metamaterial resonators as bandpass filters and other components that enable control of guided surface electromagnetic waves. The guided surface electromagnetic wave propagates on a planar Goubau line, launched via a coplanar waveguide coupler with 50 impedance. Experimental samples targeted for either microwave or terahertz frequencies are measured and shown to be in excellent agreement with simulations. Metamaterial elements are designed to absorb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 28 publications
(30 reference statements)
0
29
0
Order By: Relevance
“…Such planar CPW-PCGL structures have advantages in integration and make it convenient to apply SSPPs to the applications of super-resolution imaging [12], electromagnetically induced transparency (EIT) [13,14], environmental detection, and bio-sensing [15,16]. At the present stage, many related investigations on the CPW-PCGL structures have been concentrated on coupling efficiency, bandwidth, transmission loss, and the enhancement of local electromagnetic field [17][18][19][20][21][22][23][24][25]. The bandwidth of SSPPs on the ultrathin PCGLs is increased significantly by reducing the depth of corrugation grooves.…”
Section: Introductionmentioning
confidence: 99%
“…Such planar CPW-PCGL structures have advantages in integration and make it convenient to apply SSPPs to the applications of super-resolution imaging [12], electromagnetically induced transparency (EIT) [13,14], environmental detection, and bio-sensing [15,16]. At the present stage, many related investigations on the CPW-PCGL structures have been concentrated on coupling efficiency, bandwidth, transmission loss, and the enhancement of local electromagnetic field [17][18][19][20][21][22][23][24][25]. The bandwidth of SSPPs on the ultrathin PCGLs is increased significantly by reducing the depth of corrugation grooves.…”
Section: Introductionmentioning
confidence: 99%
“…High Q-factor sensors are expected to detect quantities of material several orders of magnitude smaller than what is currently demonstrated. Some future possibilities include combining benefits of high Q-factor resonators with thin membrane substrates, or employing single SRRs inside a waveguide, or coupled to microstrip lines [125,126]. By using single SRRs, a thin-film sample need only cover about 4 μm 2 , instead of the normal area of a terahertz MM (≈0.5 cm 2 ).…”
Section: High Q-factor Metamaterialsmentioning
confidence: 98%
“…J. Pendry et al reported that structured metal surface can support and propagate SSPPs [7]. In order to produce high transmission efficiency between single wire and coplanar waveguide (CPW), many efforts have been made [11][12][13][14]. As we know, SSPPs have good characteristics of high field confinement, planar configuration and deep-subwavelength, so we can take the advantage of the SSPPs to fabrication circulator.…”
Section: Introductionmentioning
confidence: 99%